Photogating Effect-Driven Photodetectors and Their Emerging Applications - Jihyun Shin; Hocheon Yoo (Nanomaterials, 2023)
Rather than generating a photocurrent through photo-excited carriers by the photoelectric effect, the photogating effect enables us to detect sub-bandgap rays. The photogating effect is caused by trapped photo-induced charges that modulate the potential energy of the semiconductor/dielectric interface, where these trapped charges contribute an additional electrical gating-field, resulting in a shift in the threshold voltage. This approach clearly separates the drain current in dark versus bright exposures. In this review, we discuss the photogating effect-driven photodetectors with respect to emerging optoelectrical materials, device structures, and mechanisms. Representative examples that reported the photogating effect-based sub-bandgap photodetection are revisited. Furthermore, emerging applications using these photogating effects are highlighted. The potential and challenging aspects of next-generation photodetector devices are presented with an emphasis on the photogating effect.